A History of Christian-Muslim Relations - Goddard, Hugh (Rowman & Littlefield Publishers, 2000)
The relationship between the Christian and Muslim worlds has been a long and tortuous one. Over the course of the centuries the balance of power has swung in pendulum fashion—at times the initiative seems to have lain with the Muslim community, with the Christian world simply being compelled to react to developments outside itself, while at other points the opposite has been true and Muslims have found themselves having to respond to Christian challenges in different forms. Today Christians and Muslims comprise the world's two largest religious communities. Although they can coexist fairly peacefully, at times they still engage in violent confrontation, such as in the recent conflicts in Bosnia and the Sudan. This book investigates the history of the relationships between Christians and Muslims over the centuries, from their initial encounters in the medieval period, when the Muslims were the dominant group, through to the modern period, when the balance of power seems to have been reversed. This much-needed overview of the Christian-Muslim encounter places the emphasis on the context within which perceptions and attitudes were worked out and provides a depth of historical insight to the complexities of current Christian-Muslim interactions on different continents.